EspaÃ±ol (Ictus, 2021)
ABSTRACTIntroductionLow socioeconomic status has been related to increased stroke incidence and bad functional outcome. Educational level has been less studied as a risk factor. We aim to determine if lower educational level or socioeconomic status are independent risk factors for worse prognosis in stroke patients in Mexico.  MethodsWe included patients with a first ischemic or hemorrhagic stroke who had at least 3 years of follow-up. Demographic, clinical and socio-cultural (income/highest education level) variables were registered. Bivariate analysis was performed to determine the impact of these factors on functional outcome, mortality, and recurrence. The resultant sariables were included in a logistic regression analysis model. ResultsWe included 544 patients with stroke (45% ischemic, 55% hemorrhagic). Factors independently related to poor functional outcome were lower educational level, HTM, DM, AF, and neurological deterioration on admission (GCS). Income and lower educational level were not independent predictor for recurrence or mortality. ConclusionLower educational level an independent risk factor for bad functional outcome after  stroke in our population. Higher incidence, less aggressive treatments and deficient follow-up and rehabilitation may be the main causes for this observation. Further studies will determine which factors are relevant and modifiable when treating stroke patients with lower educational levels.